Despesa pública no Ministério Público da Paraíba: melhoria do processo - Cesário, Marcos Vinicius Ferreira (2019)
The work processes of the Attorney General's Office are essential for the administrative success of the Paraíba Public Prosecutor's Office (MPPB). If the workflow management of these processes is efficient, a clearer and more comprehensive view of management can be offered, better control and monitoring of activities performed and improvements in organizational performance. The main objective of this technical report is to analyze the process of execution of public expenditure within the scope of the Public Prosecution Service of Paraíba, based on ISO / TR 26122 and the laws governing the process, applying the business process management model and submitting the process. the method of earned value analysis. From this perspective, we work with the following research problem: How can the flow of the public expenditure execution work process of the Paraíba Public Prosecution Service be optimized based on the value added analysis method? The study brings as theoretical support concepts about Process Management. It also explores the Business Process Management (BPM) method, with approaches in Business Process Model and Notation (BPMN) and Business Process Management Suite or System (BPMS), as well as proposing forms of qualitative process analysis. Finally, after due flow analysis based on ISO TR 26122 and the earned value analysis method, it is reported that approximately 67% of the Contract Payment Notification Work Process activities were categorized as No Added Value, making it possible to know the purpose and operation of the contract payment notification process, covering all flows, activities, legislations and responsible parties involved, as well as all information and records necessary to complete the process.